Smooth, striated, or rough: how substrate textures affect the feeding performance of tadpoles with different oral morphologies - Annibale, Fabiane Santana; de Sousa, Verônica Thiemi Tsutae; de Sousa, Carlos Eduardo [UNESP]; Venesky, Matthew D.; Rossa-Feres, Denise de Cerqueira [UNESP]; Wassersug, Richard J.; Nomura, Fausto (Springer Nature, 2020)
For grazing animals that share spatial and alimentary resources, the relationship between differences in oral morphology and the physical properties of substrates can help explain how and where species forage. The substrates may require different efforts from animals to access and remove food from their surfaces. Variation in oral morphology may produce differences in animals’ feeding efficiency. We tested whether one substrate characteristic, the surface texture (i.e., smooth, striated and rough), influences the growth and food consumption rates of anuran larvae from nine species with different oral morphologies. Tadpoles with few keratinized oral structures and those with more gaps in the marginal papillae row were more efficient grazing on smooth and rough surfaces, respectively. This may indicate possible feeding specializations. Conversely, tadpoles with a high number of labial tooth rows, regardless of the number of gaps in these structures, and those with only a dorsal gap in the marginal papillae row were equally efficient feeding upon all substrate textures. Tadpoles with the generalized labial tooth row formula 2(2)/3(1), had higher growth rates than the other species, suggesting an adaptive significance for this common oral morphology. We demonstrated that species differ in feeding efficiency when grazing on substrates with different textures. This can help elucidate the adaptive significance of variation in tadpole oral morphology. We also provide insights on resource selection and niche partitioning among species, especially for those whose diets do not differ in quantity or quality, as it is common in anuran larval assemblages.
Keywords: Anuran larvae; Ecomorphology; Feeding behavior; Foraging surfaces; Niche breadth